The European Higher Education Area: A road to the future or at way's end? - Sjur Bergan (Universidad de Deusto, 2019)
The goal of the Bologna Process was to develop a European Higher Education Area within a decade. The goal and the process proved to be attractive, new countries steadily applied for accession, and the Bologna Process has brought about substantial reforms. At the same time, the drive and optimism of the early years has given way to more measured optimism and even a sense of disillusion as we approach the 20th anniversary of the Bologna Declaration. The article outlines six phases in the development of the European Higher Education Area and then looks at some of the main challenges the EHEA faces as it approaches its third decade. Structural reforms have been the hallmark of the EHEA, and in this area the main challenges concern implementation rather than the development of new structures even if some policy challenges also remain. In the run-up to the 2018 Ministerial conference, EHEA faced a bitter debate on the character of the EHEA itself, linked to the questions of how to foster implementation of commitments undertaken and what it means to be a voluntary process. The fundamental values on which the EHEA builds are now threatened in some EHEA members, the role of the EHEA in a global context, and its relevance and governance constitute other challenges. Received: 08 April 2019 Accepted: 29 April 2019 Published online: 29 May 2019